An Overview of Circulating Pulmonary Arterial Hypertension Biomarkers - Santos-Gomes, Joana; Gandra, Inês; Adão, Rui; Perros, Frédéric; Brás-Silva, Carmen (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary arterial hypertension (PAH), also known as Group 1 Pulmonary Hypertension (PH), is a PH subset characterized by pulmonary vascular remodeling and pulmonary arterial obstruction. PAH has an estimated incidence of 15 to 50 people per million in the United States and Europe, and is associated with high mortality and morbidity, with patients' survival time after diagnosis being only 2.8 years. According to current guidelines, right heart catheterization is the gold standard for diagnostic and prognostic evaluation of PAH patients. However, this technic is highly invasive, so it is not used in routine clinical practice or patient follow-up. Thereby, it is essential to find new non-invasive strategies for evaluating disease progression. Biomarkers can be an effective solution for determining PAH patient prognosis and response to therapy, and aiding in diagnostic efforts, so long as their detection is non-invasive, easy, and objective. This review aims to clarify and describe some of the potential new candidates as circulating biomarkers of PAH.